The Investigation of Beam Discontinuities In Reinforced Concrete Structures With Shear-Wall Frame System in Terms of Effective Inter-Storey Drift and Second Order Effects - Seven, Sedat; Keleşoğlu, Ömer (Muş Alparslan Üniversitesi, 2018)
The reduction of beams in buildings with facade console, frequently built in Turkey, cause beam discontinuities. Active beams carrying of horizontal loads under the effect of earthquake may have negative consequences on the performance of the structure, if they have discontinuity. In this study 8, 10 and 12-story structures with the same story but different structural models (regular, console, console and mobile facade, and irregular) were analyzed using Mode Superposition Method in STA4CAD software from the standpoint of “Regulations for the Buildings in Earthquake Zones” (DBYBHY-2007) and of beam discontinuities. The results were compared according to effective inter-storey drift and second order effects. At the end of the study, it was observed that models with beam discontinuity reached higher values and approached the limit values.

Türkiye’de sıklıkla inşa edilen çıkmalı yapılardaki kirişlerin eksiltilmesi, kiriş süreksizliklerine sebep olmaktadır. Deprem etkisi altında yatay yüklerin taşınmasında aktif görev yapan kirişler, süreksiz olması durumunda yapı performansı üzerinde olumsuz sonuçlar doğurabilmektedir. Bu çalışmada perde-çerçeve taşıyıcı sisteme sahip 8, 10 ve 12 kattan oluşan yapı modelleri (düzenli, çıkmalı, çıkma ve cephe hareketli, düzensiz) olarak dört farklı durumda irdelenmiştir.  Modellerdeki kiriş süreksizliği dikkate alınarak, Deprem Bölgelerinde Yapılacak Binalar Hakkında Yönetmelik (DBYBHY-2007) doğrultusunda, mod Birleştirme Yöntemi ile STA4CAD paket programı kullanılarak analiz edilmiştir. Elde edilen sonuçlar etkin göreli kat ötelemeleri ve ikinci mertebe etkileri bakımından karşılaştırılmıştır. Çalışmanın sonunda kiriş süreksizliğine sahip modellerin daha büyük değerlere ulaştığı ve sınır değerlere yaklaştığı görülmüştür.
Betonarme Perde Çerçeveli Yapılardaki Kiriş Süreksizliğinin Etkin Göreli Kat Ötelemeleri ve İkinci Mertebe Etkileri Bakımından İrdelenmesi
Keywords: Engineering; Mühendislik